PENGARUH MOTIVASI, TEAM WORK, DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI BALAI PENGAMANAN DAN PENEGAKAN HUKUM LINGKUNGAN HIDUP DAN KEHUTANAN WILAYAH SUMATERA - TOMMY PURBA, TOMMY; Tanjung, Aldi Arizki (JEBIM Prima, 2024)
The objective of this study is to ascertain the impact of motivation, teamwork, and work discipline on employee performance at the Environmental Law Enforcement and Forestry Security Office in Sumatra. In this study a quantitative descriptive methodology was used. The research encompasses a population of 350 individuals, from which a sample of 100 has been chosen. The independent variables consist of Motivation (X1), Teamwork (X2), and Work Discipline (X3), and the dependent variable is Work Performance (Y). In this study the datas were analyzed using multiple linear regression. The research findings indicate that Motivation and Work Discipline have a substantial influence on staff performance at the Environmental Law Enforcement and Forestry Security Office in Sumatra. The results suggest that motivation, cooperation, and work discipline collectively account for 68.2% of the influence on employee performance at the Environmental Law Enforcement and Forestry Security Office in Sumatra. The remaining 31.8%.